Gender analysis of agricultural extension policies in Uganda: informing practice?. (4th May 2019) - Mpiima, David Mugambe; Manyire, Henry; Kabonesa, Consolata; Espiling, Margareta
Abstract: In Uganda, agricultural-related policies clearly commit to a Gender and Development (GAD) approach but in many cases, the praxis follows a Women in Development (WID) approach. The same approach cascades into the operations of nonstate actors like Civil Society Organizations (CSOs). Using extensive document review and a gender analysis of key policy documents in Information Communication Technology (ICT) enabled agricultural practice, the article focuses on ways CSOs take up government policies on ICT and agricultural information to improve farmers' access to agricultural information. Findings show that the government still opts for the male-dominated traditional agricultural extension system. CSOs, in contrast, have adopted a more democratized approach that allows more women to directly access extension services using mobile phones and radios. Whereas the initial aim is a focus on women, men have been allowed to participate in CSO-enabled agricultural information access, challenging the negative gender relations surrounding agriculture, and ICTs that include threats of domestic violence and the refusal of women to use technologies. Breaking these barriers has resulted into better access to agricultural information, more benefits through increased production, access to markets, and income, and more land for women and men alike.